Safety, occupational health and labor performance of personnel in a public project in the COVID-19 period - Espinoza Vidaurre, Sam Michael (2023)
The purpose of this study was to determine the influence of occupational health and safety variables on the work performance of personnel at the Proyecto Especial Tacna (Tacna Special Project), a Peruvian public institution, during the COVID-19 pandemic. To carry out the study, a quantitative, descriptive, and correlational non-experimental design was used with a census sample, a questionnaire was applied to 42 workers in the months from July to August 2022. For the analysis of the results, the statistical technique of a simple linear regression model was applied to investigate the relationships of both variables to prove the hypotheses according to the dimensions studied. The study findings showed that there is a significant relationship between occupational health and safety; and the work performance of the organization's personnel with a value of 0.792. Therefore, there is a need to incorporate a safety plan and improve safety conditions to increase work performance.